Análise dos aspectos que impactam o planejamento vertical: estudo de casos múltiplos - Lima, Ana Luiza Rabêlo Santa Rosa; Cruz, Herbert Melo; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Vertical planning is the hierarchy of planning at long, medium and short term levels. Therefore, the main aim of this research was to develop analyzes about the positive and negative aspects in these levels in multi-paving works. A multi-case study involving three works located in the state of Sergipe, was carried out, collecting data through semi-structured interview and observation. As a results, positives and negatives aspects regarding the vertical planning of the works were obtained. The positive aspects identified are linked to the insertion of the principles of planning and control of works prior to its start and during its execution. On the other hand, the lack of interaction between planning levels is caused by the lack of daily actions in multi-floor buildings, but these can interfere directly with factors such as productivity and deadlines. The results presented in this paper confirmed the initial hypothesis of the presence of vertical planning failures originated from informality.